Mengatasi Rendahnya Partisipasi Siswa: Transformasi Pembelajaran PPKn melalui Model Kooperatif untuk Mewujudkan Kelas Kolaboratif - Muzayyin Muzayyin; Linda Ramadhanty Januar; Arwani Arwani (Jurnal Cendekia Pendidikan, 2026)
This study aims to examine (1) the implementation of Pancasila Education instruction using the cooperative learning model and (2) the improvement of learning outcomes through this model in Grade VII at SMP Al-Ismailiyah. This study is a Classroom Action Research (CAR) project. The subjects were all 30 students in the Grade VII class. The intervention applied to improve learning outcomes in Pancasila Education was the cooperative learning model. The research findings are as follows: (1) the implementation of Pancasila Education instruction using the cooperative learning model adhered to established instructional procedures; (2) the class average score improved from an initial test average of 54.4 (with a mastery rate of 13.3%) to an average of 75 in Cycle I (with a mastery rate of 48.67%) and an average of 80 in Cycle II (with a mastery rate of 85%); and (3) student learning outcomes improved from the initial test through to Cycle II. Based on the results of Cycle II, the research action was concluded, as the expected improvements had been achieved. It can be concluded that the cooperative learning model is an effective method for enhancing the quality of classroom instruction. By actively involving students in the learning process, this method helps deepen their understanding of the material, sharpens critical and creative thinking skills, and fosters social interaction among students. Therefore, cooperative learning should be adopted as an effective and enjoyable instructional strategy.